Structure of choline chloride-carboxylic acid deep eutectic solvents by wide-angle X-ray scattering and DFT calculations. Issue 15 (29th March 2023) - Chai, Keke; Zhou, Yongquan; Lu, Xingmei; Yamaguchi, Toshio; Ohara, Koji; Liu, Hongyan; Zhu, Fayan
Abstract : Choline possesses a gauche configuration in choline chloride-carboxylic acid DESs. DESs are stabilized by hydrogen bonds and carbon–hydrogen bonds. Cl − plays an important role in maintaining the structural stability of DESs. Abstract : Choline chloride (ChCl)-carboxylic acid deep eutectic solvents (DESs) are promising green solvents for lignocellulose pretreatment, de-aromatization of gasoline, battery recycling, etc. Micro interactions determine the physical properties of DESs, such as melting point, viscosity, and solubility. In the present work, the structures of choline chloride/formic acid (FA) and choline chloride/acetic acid (AA) with a 1 : 2 molar ratio were investigated by wide-angle X-ray scattering, empirical potential structure refinement (EPSR) and density functional theory (DFT) calculations. Reduced density gradient (RDG) and atoms in molecules (AIM) show that hydrogen bonds and carbon–hydrogen bonds exist in choline chloride–carboxylic acid DESs. EPSR modelling based on the gauche choline cation model reveals the interactions between DES components. Cl − plays an important role in maintaining the structural stability of choline chloride–carboxylic acid DESs, by participating in the formation of hydrogen bonds, carbon–hydrogen bonds, and acting as a bridge for indirect interaction, including between choline cations and carboxylic acid molecules. Molecular size and steric hindrance elucidate the formation of different sizes of clusters (≤10 molecules) and chains (≤5 molecules) in DESs. Spatial density functions show that formic acid and acetic acid have a strong orientational preference. The strong interaction between Ch + and FA and the existence of the Cl − bridge significantly destroyed the lattice structure of ChCl, resulting in the melting point of ChClFA (<−90 °C) being lower than that of ChClAA (−8.98 °C). This fundamental understanding of the structure will enable the development of green, economical, and nontoxic choline chloride–carboxylic acid DESs.